2002
DOI: 10.1071/wf02037
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of wildfire on soil hydrological properties of steep sagebrush-steppe rangeland

Abstract: In late August 1996, a wildfire swept across the sagebrush-dominated foothills above Boise, Idaho. Fire impacts on infiltration and inter-rill erosion were examined 1 year following the fire with simulated rainfall. Densely vegetated north-facing slopes were compared with sparsely vegetated south-facing slopes under both burned (moderate and high severity) and unburned conditions. Both fire severity and slope aspect strongly influenced the impact of fire on infiltration capacity and soil erodibility. South-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 11 publications
5
71
0
Order By: Relevance
“…Therefore, there did not appear to be a substantial effect of burning on microsite morphology. This suggests that physical and/or biological mechanisms (i.e., wind or water transport, ungulate trampling, burrowing, annual grass, or woody plant invasion) in addition to burning might be required to alter microsite morphology (Pierson et al, 1994(Pierson et al, , 2001(Pierson et al, , 2002Hilty et al, 2003;Li et al, 2008;Ravi et al, 2009;Field et al, 2010;Sankey et al, 2010). Nonetheless, roughness and the average height difference between undershrub and interspace microsites appeared to vary amongst sites (Figs.…”
Section: Effectmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, there did not appear to be a substantial effect of burning on microsite morphology. This suggests that physical and/or biological mechanisms (i.e., wind or water transport, ungulate trampling, burrowing, annual grass, or woody plant invasion) in addition to burning might be required to alter microsite morphology (Pierson et al, 1994(Pierson et al, , 2001(Pierson et al, , 2002Hilty et al, 2003;Li et al, 2008;Ravi et al, 2009;Field et al, 2010;Sankey et al, 2010). Nonetheless, roughness and the average height difference between undershrub and interspace microsites appeared to vary amongst sites (Figs.…”
Section: Effectmentioning
confidence: 98%
“…3). We expected that undershrub soil surfaces would be rougher than interspaces based on abundant literature that describes a wider range of particle and aggregate sizes and densities for undershrubs relative to interspaces (Blackburn, 1975;Roundy et al, 1978;Wood et al, 1978Wood et al, , 1982Doescher et al, 1984;Johnson and Gordon, 1988;Blackburn et al, 1990Blackburn et al, , 1992Bolton et al, 1990;Goff et al, 1993;Pierson et al, 1994Pierson et al, , 2001Pierson et al, , 2002Davies et al, 2007Davies et al, , 2009Aanderud et al, 2008;Hooker et al, 2008) as well as the greater proportion of organic matter on the undershrub soil surfaces that we characterized. Furthermore, interspaces often have a physical crust with a relatively flat, smooth appearance that is in sharp contrast, visually, to raised undershrub mounds (Blackburn, 1975;Roundy et al, 1978;Wood et al, 1978Wood et al, , 1982Doescher et al, 1984;Johnson and Gordon, 1988;Blackburn et al, 1990Blackburn et al, , 1992Bolton et al, 1990;Goff et al, 1993;Pierson et al, 1994Pierson et al, , 2001Pierson et al, , 2002Davies et al, 2007Davies et al, , 2009Aanderud et al, 2008;Hooker et al, 2008).…”
Section: Microsite Roughness Morphology and Burningmentioning
confidence: 99%
“…Bioturbation associated with ant mounding and animal scratchings by animals has been shown to significantly increase erosion on plots subjected to fires of moderate intensity in eastern Australia (Dragovich and Morris, 2002). Pierson et al (2002) found an interaction between fire severity and slope aspect on infiltration capacity and soil erodibility using rainfall simulation. Fire severity had little effect on infiltration and erosion on northfacing slopes while on south-facing slopes infiltration rate was significantly less, and cumulative sediment yield was significantly greater on severely burnt compared to moderately burnt plots.…”
Section: Experimental Plotsmentioning
confidence: 93%
“…This demonstrates the importance of estimating risks to physical attributes of the ecosystem that support the biota. For example, rates of soil erosion or nitrogen and carbon loss have been shown to be positively correlated with fire intensity (Shakesby et al, 1993;Pierson et al, 2002) and have a direct impact on vegetation growth rates (Baird et al, 1999). Furthermore, the time-scale at which the risk is being assessed (decades to centuries) must be clearly identified prior to initiation of the assessment, as temporal changes in system response result in differing risk predictions depending upon the time frame.…”
Section: Application To Uncharacteristic Wildfiresmentioning
confidence: 99%